Hubungan Konsumsi Pakan Dengan Pertumbuhan dan Konversi Pakan Broiler Pada Kemitraan PT Mitra Sinar Jaya - Ufie, Emerikus Krisna; Malle, Dominggus; Hehanussa, Sylvia Ch H (Jurnal Agrosilvopasture-Tech, 2024)
This research aims to determine the relationship between feed consumption and growth and feed conversion of broilers in the PT Mitra Sinar Jaya partnership. The research material is the broiler strain CP-707 which is kept in open house cages with a population of 6,500 in the 4 cages and commercial feed S10, S11, and S12. This panel research was carried out for 35 days and reared broilers at PT Mitra Sinar Jaya partnership breeders in Seri Village, Nusaniwe District, Ambon City. The method used in this research is survey and observation (direct observation in the field) to collect data related to the performance of the CP-707 broiler strain. The variables observed in this research were feed consumption, body weight gain, and feed conversion ratio (FCR). The data obtained was analyzed using a simple linear regression method. The research results showed a relationship between feed consumption and body weight gain and feed conversion ratio (FCR) with R2 values ​​of 0.9802 and 0.0228 respectively, with an average feed consumption of 514.13 g/head, UN of 311 .04 g/head, and an FCR value of 1.65.